International Trade and North-Sumatra’s Local Economy - Tampubolon, Jongkers; Nababan, Tongam Sihol (Universitas Negeri Semarang, 2018)
North Sumatra is one of the provinces in Indonesia with high levels of economic openness. On average, since 2000, the contribution of export value to the Regional GDP reached 40 % and import value of 28%. Using Granger causality method, the study aims to investigate causal relations between international trade and North Sumatra’s local economy especially the impact of exports and imports on Regional GDP, Regional GDP per capita, employment and poverty reduction. The empirical results of present study discovered that (i) the exports and imports respectively have positive and significant impact on regional GDP, regional GDP per capita, employment and poverty reduction, (ii) there is a bi-directional causality between imports and regional GDP, where GDP growth rate would boost imports over-proportionally, (iii) both exports and imports are dominated by intermediate goods as the raw materials for further processing industry, (iv) export structure which is dominated by the agricultural-based intermediate good is proverty-reduction through factor market in the upstream sector making the rural peoples benefited from the exports.